Humanitarian NGO-networks: Identifying powerful political actors in an international policy field - Yasemin Topçu (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
Humanitarian assistance is a growing policy-field, where the humanitarian nongovernmental actors gained a new, politically influential role. These actors have established networks in order to increase and facilitate cooperation and coordination mechanisms among them. This study identifies a number of humanitarian NGO-networks which actively participate in humanitarian policy decision-making processes. In order to identify the common motives and (political) interests of humanitarian NGO-networks a cross-section of internationally active humanitarian NGOs is identified. A typology of international humanitarian NGOs is starting with an analysis of German humanitarian NGOs. The analysis of the humanitarian networks shows that contrary to the often propagated cooperation between Northern and Southern non-governmental actors this is actually not realized at the network level. There, NGOs of the industrialized West, i.e. from the donor countries, are the almost exclusive participants in the humanitarian decision-making process. – – Humanitäre Hilfe ist ein im Wachsen begriffenes Politikfeld, in dem die humanitären nichtstaatlichen Akteure eine neue politisch einflußreiche Rolle einnehmen. Diese Akteure sind inzwischen in Netzwerke organisiert, um die Kooperation und Koordination zwischen ihnen zu erhöhen und zu erleichtern. In dem Papier wird eine Anzahl humanitärer NGO-Netzwerke identifiziert, die aktiv an Entscheidungsprozessen humanitärer Politik beteiligt sind. Aus einem Querschnitt von international tätigen humanitären NGOs werden die gemeinsamen Motive und (politischen) Interessen humanitärer NGO-Netzwerke herausgearbeitet. Mittels einer Analyse deutscher Hilfsorganisationen wird eine Typologie internationaler humanitärer NGOs entwickelt. Die Analyse der humanitären Netzwerke läßt den Schluß zu, daß die viel beschworene Kooperation zwischen nicht-staatlichen Akteuren des Nordens und des Südens auf jener Netzwerkebene nicht umgesetzt wird. Vielmehr nehmen dort die NGOs des industrialisierten Nordens, d.h. aus den Geberländern, eine eher exklusiv partizipatorische Rolle im Entscheidungsprozeß zu humanitärer Hilfe ein.
Keywords: 320